Gynecological correlation of thyroid disorders in women - R., Pooja; Patil, Varsha Narendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Thyroid dysfunctions are a common cause of abnormal uterine bleeding (AUB). They affect menstrual function and reproductive health. The common presenting complaints are weight gain, menstrual irregularities, PCOS, infertility, fatigue, constipation and body aches. In this study we recommended that any woman presenting with undiagnosed fatigue, weight gain, infertility and menstrual disorders should be subjected to Thyroid profile screening. Thus, there is a need to explore this aspect in the earlier stages so as to prevent long term consequences with reproduction and quality of life. Methods: Current study is a retrospective study. The present study was conducted in the department of obstetrics and gynecology, Cama and Albess hospital, Mumbai, Maharashtra, India, from a period of January 2021 to December 2021, 300 women of reproductive age group between menarche to menopause. Quantitative determination of Serum T3, T4 and TSH by CLIA estimated in autoanalyser. Results: The most common age group studied was between 32-40 years. Hyperthyroidism was more common in multipara and hypothyroidism was more common in P2L2. The most common type of menstrual disturbance was menorrhagia. (40.33%) Menorrhagia has been seen to have significant association with thyroid dysfunction. Prevalence of obesity in the study population is 4% and overweight is 23.66%. About 11.33 % of overweight women and 2% of obese women are hypothyroid. 2% of hyperthyroid women are underweight (BMI<18). About 6.33% of women with hypothyroidism had PCOS, most commonly associated with menstrual complaints such as amenorrhoea and oligomenorrhoea. 14% of women with hypothyroidism had clinical findings of anaemia and/or thyromegaly on clinical examination. 14% of women had severe anaemia in the study group, out of which 6.7% of hypothyroid women had severe anaemia. 3.66% women presented with infertility. Conclusions: Biochemical evaluation of thyroid function tests should be compulsory in all patients with menstrual irregularities, PCOS, infertility, fatigue, body aches, anaemia, thyromegaly, weight gain, constipation to detect thyroid dysfunction.